Preoperative Use of Erythropoietin as a Mean of Blood Saving in Children with Nonsyndromic Craniosynostosis - G. Z. Sufiyanova; N. E. Ivanova; A. A. Sufiyanov; S. S.-K. Gayibov (Педиатрическая фармакология)
It is known that neurosurgical operations are characterized by blood loss requiring hemotransfusion. At the same time, world practice oversees a tendency towards restricted use of donor blood components for this purpose. This has become possible through the use of various blood saving methods, including use of erythropoietin-based drugs. This review is dedicated to analysis of the modern research data on preoperative use of erythropoietin-based drugs in combination with iron preparations in patients with nonsyndromic craniosynostosis requiring surgical correction. It has been demonstrated that preoperative (2–3-week-long) administration of erythropoietin allows limiting hemotransfusion and reducing the amount of intraoperatively transfused donor blood. Based on these data, we assume that erythropoietin is an effective and safe alternative to the “standard” means of blood saving, such as normovolemic hemodilution, controlled hypotension, automatic blood sampling and reinfusion of the patient’s erythrocytes.